Pelatihan “INTERAKTIF” Meningkatkan Empati Guru BK - Risa Harisah; Neila Ramdhani (Gadjah Mada Journal of Professional Psychology (GamaJPP), 2018)
The “INTERAKTIF” training was compiled to increase the empathy of a school counselor in assisting their students. The “INTERAKTIF” module consists of emotional intelligence and therapeutic communication theory. The research was conducted by untreated control group design method with dependent pretest and posttest samples, which include experimental group and control group. Participants in this research consist of 46 junior high school counselors in Yogyakarta. Statistical analysis result using Mixed ANOVA showed that empathy level on experiment group significantly differs from the control group (F=4,805, p = 0,034). The final result shows that the “INTERAKTIF” training effective in increasing the junior high school counselor’s empathy in Yogyakarta.